Habits are stronger with longer duration of illness and greater severity in anorexia nervosa. Issue 5 (30th March 2020) - Davis, Lauren; Walsh, B. Timothy; Schebendach, Janet; Glasofer, Deborah R.; Steinglass, Joanna E.
Abstract: Objective: The aim of this study was to examine the relationship between habit strength and clinical features of anorexia nervosa (AN). Habit strength, separate from intention, relates to the persistence of behavior, and is measured by the Self‐Report Habit Index (SRHI). We hypothesized that habit strength would be greater among individuals with AN than healthy controls (HC) and that habit strength would be associated with duration and severity of illness. Method: Participants were 116 women with AN ( n = 69) and HC ( n = 47) who completed the SRHI, the Eating Disorder Examination‐Questionnaire (EDE‐Q), and a multi‐item laboratory meal. The SRHI assessed four domains and these subscales were averaged for the total score. Results: Individuals with AN demonstrated significantly greater habit strength than HC in the total score ( t 114 = 7.00, p < .01), and within each domain (restrictive eating, compensatory behavior, delay of eating, and rituals). Total SRHI score was significantly associated with EDE‐Q scores for both AN and HC groups ( r AN = .59, p AN = <.001; r HC = .32, p HC = .030). Among patients, there was a significant association between SRHI and duration of illness ( r = .38, p = .001). There was no significant association between SRHI and caloric intake ( r AN = −.20, p AN = .10; r HC = −.25, p HC = .09). Discussion: Habit strength was related to chronicity and severity of AN, suggesting that habit formation may play an important role in illness. These data suggest avenues for mechanism research and treatment development.